Autoreactive thymic B cells are efficient antigen-presenting cells of cognate self-antigens for T cell negative selection - Perera, Jason (National Academy of Sciences, 2013)
The thymus contains a population of B cells that colocalize with dendritic cells and medullary thymic epithelial cells in the thymic medulla. The development and functional significance of these cells are largely unknown. Using recombination-activating gene 2 GFP reporter mice along with parabiosis experiments, we demonstrate that the vast majority of thymic B cells develop from progenitors within the thymus. Thymic B cells express unique phenotypic markers compared with peripheral B cells; particularly they express high levels of MHC class II, suggesting that they are poised to present self-antigens efficiently. Using Ig knock-in and T-cell receptor transgenic mice specific for the self-antigen glucose-6-phosphate isomerase, we show that autoreactive thymic B cells serve as efficient antigen-presenting cells for T cell negative selection even when they are present at low frequencies. Furthermore, the endogenous thymic B-cell repertoire also functions in this capacity. These results suggest that developing thymic B cells could efficiently capture a broad array of autoantigens through their B-cell receptors, presenting peptides derived from those autoantigens to developing thymocytes and eliminating cognate T cells.